Bronchoalveolar lavage fluid of lung cancer patients: mapping the uncharted waters using proteomics technology - Oumeraci, Tonio; Schmidt, Bernd; Wolf, Thomas; Zapatka, Marc; Pich, Andreas; Brors, Benedikt; Eils, Roland; Fleischhacker, Michael; Schlegelberger, Brigitte; Neuhoff, Nils v. (Lung cancer, 2011)
NSCLC; Bronchoalveolar lavage fluid; Biomarkers; MALDI-TOF mass spectrometry; Bioinformatics; Proteomics